In vivo chlorophyll fluorescence screening allows the isolation of a Chlamydomonas mutant defective for NDUFAF3, an assembly factor involved in mitochondrial complex I assembly. (28th September 2017) - Massoz, Simon; Hanikenne, Marc; Bailleul, Benjamin; Coosemans, Nadine; Radoux, Michèle; Miranda‐Astudillo, Hector; Cardol, Pierre; Larosa, Véronique; Remacle, Claire
SUMMARY: The qualitative screening method used to select complex I mutants in the microalga Chlamydomonas, based on reduced growth under heterotrophic conditions, is not suitable for high‐throughput screening. In order to develop a fast screening method based on measurements of chlorophyll fluorescence, we first demonstrated that complex I mutants displayed decreased photosystem II efficiency in the genetic background of a photosynthetic mutation leading to reduced formation of the electrochemical proton gradient in the chloroplast ( pgrl1 mutation). In contrast, single mutants ( complex I and pgrl1 mutants) could not be distinguished from the wild type by their photosystem II efficiency under the conditions tested. We next performed insertional mutagenesis on the pgrl1 mutant. Out of about 3000 hygromycin‐resistant insertional transformants, 46 had decreased photosystem II efficiency and three were complex I mutants. One of the mutants was tagged and whole genome sequencing identified the resistance cassette in NDUFAF3, a homolog of the human NDUFAF3 gene, encoding for an assembly factor involved in complex I assembly. Complemented strains showed restored complex I activity and assembly. Overall, we describe here a screening method which is fast and particularly suited for the identification of Chlamydomonas complex I mutants. Significance Statement: In pgrl1 background, photosystem II quantum yield strongly depends on mitochondrial respiration, and can be successfully used for fast screening of complex I mutants. A small‐scale pilot insertional library allowed the isolation of a mutant affected in NDUFAF3 coding for a complex I assembly factor.